2019
DOI: 10.1016/j.ijscr.2019.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral posterior hip dislocation associated with right Pipkin II fracture: A case report

Abstract: Highlights Bilateral posterior hip dislocations are very rare injury, resulting from high energy trauma. After elimination of vital emergencies and radiological assessment, reduction must be rapid within 6 h. Post reduction CT-scan is essential to analyze the femoral head and the hip joint congruity. In case of irreducibility or associated Pipkin’s fracture, an open approach is indicated. The main complications are ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
3
Order By: Relevance
“…After twelve months, the results showed an excellent hip function and no radiographic evidence of avascular necrosis. More recently, Zaizi et al 8 reported good results with the treatment of Pipkin type-II fractures using anatomical reduction and internal fixation by means of two Herbert screws, after two years of follow-up. Wang et al, 11 in a prospective analysis of three patients treated using Herbert screws, reported results of satisfactory hip function assessed by the modified Merle d'Aubigné score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After twelve months, the results showed an excellent hip function and no radiographic evidence of avascular necrosis. More recently, Zaizi et al 8 reported good results with the treatment of Pipkin type-II fractures using anatomical reduction and internal fixation by means of two Herbert screws, after two years of follow-up. Wang et al, 11 in a prospective analysis of three patients treated using Herbert screws, reported results of satisfactory hip function assessed by the modified Merle d'Aubigné score.…”
Section: Discussionmentioning
confidence: 99%
“…Type-II lesions present great controversy regarding approach and fixation models, with little scientific research. 2 3 8 9 10 11 Previous studies (case reports and retrospective analyses) show favorable results with the use of cortical screws of minifragment (measuring between 2.0 mm and 2.4 mm) 9 and Herbert screws. 8 10 On the other hand, despite their differentiated compression capacity compared to that of other syntheses and their wide clinical use, 3-mm canulated screws have been associated with a greater predisposition to develop osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bilateral symmetric hip dislocations are exceedingly uncommon and are frequently accompanied by acetabular fractures [2]. It is imperative that a dislocated hip be reduced within 6 hours to prevent avascular necrosis of the hip [3,4]. The reduction can be either closed or open if associated with a femoral head or acetabular fracture.…”
Section: Introductionmentioning
confidence: 99%